Gorgeous Pedagogy - Debra Castillo (Studies in 20th & 21st Century Literature, 1996)
Elena Poniatowska's recent Luz y luna, Ias lunitas immediately impresses the reader with its beauty; it is akin to a "coffee table book" in its sheer gorgeousness. I intend to explore the question of how to read the gorgeous object within the context of Poniatowska's oeuvre and within the frame of a pedagogical endeavor. Poniatowska, of course, represents the epitome of the elite but socially conscious Latin American author. As in certain of her other works (but perhaps more obviously here, because of the very nature of this book), the mix of elitism and social consciousness undergoes a multiple displacement. Like her other works, Luz y Iuna constitutes a palimpsest of discourses, seems to partake more of the modern semi-autobiographical gender essay than of the traditional (male) essay, and explicitly addresses the challenge of feminism in a Latin American setting. Nevertheless, this social consciousness enters into an implicit conflict with two of the book's other fundamental qualities: its polished and lyrical approach to the people and landscape of Mexico, and its utopian nostalgia, especially with respect to Mexico's indigenous cultures. In essence, then, this paper will explore how—more clearly than in her less overtly polished works—the problem of a pedagogical model drawn from Poniatowska is highlighted in this text.
Keywords: Elena Poniatowska; Luz y luna las lunitas; beauty; pedagogy; elite; society; social consciousness; gender; feminism; Latin American Feminism; Mexico